Embryonic Cerebrospinal Fluid Increases Neurogenic Activity in the Brain Ventricular-Subventricular Zone of Adult Mice - Alonso, Maria I.; Lamus, Francisco; Carnicero, Estela; Moro, Jose A.; de la Mano, Anibal; Fernández, Jose M. F.; Desmond, Mary E.; Gato, Angel (Frontiers in Neuroanatomy, 2017)
Neurogenesis is a very intensive process during early embryonic brain development, becoming dramatically restricted in the adult brain in terms of extension and intensity. We have previously demonstrated the key role of embryonic cerebrospinal fluid (CSF) in developing brain neurogenic activity. We also showed that cultured adult brain neural stem cells (NSCs) remain competent when responding to the neurogenic influence of embryonic CSF. However, adult CSF loses its neurogenic inductive properties. Here, by means of an organotypic culture of adult mouse brain sections, we show that local administration of embryonic CSF in the subventricular zone (SVZ) niche is able to trigger a neurogenic program in NSCs. This leads to a significant increase in the number of non-differentiated NSCs, and also in the number of new neurons which show normal migration, differentiation and maturation. These new data reveal that embryonic CSF activates adult brain NSCs, supporting the previous idea that it contains key instructive components which could be useful in adult brain neuroregenerative strategies.